Answer:
1. <em>Axis of symmetry</em>: x = 3
2. <em>Vertex:</em> (3,5)
3. <em>Solution of the equation</em>:
<u />
![(3-\sqrt{5},0) \\\\(3+\sqrt{5},0)](https://tex.z-dn.net/?f=%283-%5Csqrt%7B5%7D%2C0%29%20%5C%5C%5C%5C%283%2B%5Csqrt%7B5%7D%2C0%29)
Explanation:
<u>1. Equation:</u>
![y=-x^2+6x-4](https://tex.z-dn.net/?f=y%3D-x%5E2%2B6x-4)
<u>2. </u><em><u>Axis of symmetry:</u></em>
That is the equation of a parabola, whose standard form is:
![y=ax^2+bx+c](https://tex.z-dn.net/?f=y%3Dax%5E2%2Bbx%2Bc)
Where:
![a=-1;b=6;c=-4](https://tex.z-dn.net/?f=a%3D-1%3Bb%3D6%3Bc%3D-4)
The axis of symmetry is the vertical line with equation:
![x=-b/2a](https://tex.z-dn.net/?f=x%3D-b%2F2a)
Substitute ![a=-1,\text{ and }b=6](https://tex.z-dn.net/?f=a%3D-1%2C%5Ctext%7B%20and%20%7Db%3D6)
![x=-6/[(2)(-1)]=-6/(-2)=3](https://tex.z-dn.net/?f=x%3D-6%2F%5B%282%29%28-1%29%5D%3D-6%2F%28-2%29%3D3)
Thus, the axis of symmetry is:
![x=3](https://tex.z-dn.net/?f=x%3D3)
<em><u>3. Vertex</u></em>
<em><u /></em>
The x-coordinate of the vertex is equal to the axys of symmetry, i.e x = 3.
To find the y-xoordinate, substitute this value of x into the equation for y:
![y=-x^2+6x-4\\\\y=-(3)^2+6(3)-4=-9+18-4=5](https://tex.z-dn.net/?f=y%3D-x%5E2%2B6x-4%5C%5C%5C%5Cy%3D-%283%29%5E2%2B6%283%29-4%3D-9%2B18-4%3D5)
Therefore, the vertex is (3, 5)
<u>4. Find the x-intercepts</u>
The x-intercepts are the roots of the equation, which are the points wher y = 0.
![y=-x^2+6x-4=0](https://tex.z-dn.net/?f=y%3D-x%5E2%2B6x-4%3D0)
Use the quadratic equation:
![x=\frac{-b\pm \sqrt{b^2-4ac} }{2a} \\\\x=\frac{-6\pm\sqrt{(-6)^2-4(-1)(-4)} }{2(-1)}\\\\x_1=3-\sqrt{5} \\\\x_2=3+\sqrt{5}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D%20%5C%5C%5C%5Cx%3D%5Cfrac%7B-6%5Cpm%5Csqrt%7B%28-6%29%5E2-4%28-1%29%28-4%29%7D%20%7D%7B2%28-1%29%7D%5C%5C%5C%5Cx_1%3D3-%5Csqrt%7B5%7D%20%5C%5C%5C%5Cx_2%3D3%2B%5Csqrt%7B5%7D)
<u>5. Find the y-intercept</u>
<u />
The y-intercet is the value of y when x=0:
![y=-x^2+6x-4\\\\y=-(0)^2+6(0)-4=-4](https://tex.z-dn.net/?f=y%3D-x%5E2%2B6x-4%5C%5C%5C%5Cy%3D-%280%29%5E2%2B6%280%29-4%3D-4)